Measurement of radon concentration in Iraqi construction workers and painter’s blood samples using CR-39 passive detectors - A Amin, Sahar; M Haleem, Azhar (International Journal of Physical Research, 2022)
Radon concentration was estimated in 44 blood samples collected from Iraqi construction workers and painters using CR-39 passive detectors. Twenty-nine of them are non-smokers and the rest are heavy smokers. The result showed that the radon concentrations in the blood samples for construction workers were ranged between 9.201 and 126.763 Bq.m-3 with an average value of 45.987 Bq.m-3. Whilst, the radon concentrations in the blood samples for painters were ranged between 2.385 and 90.983 Bq.m-3 with an average value of 43.664 Bq.m-3. The uranium concentrations in the blood samples for construction workers and painters were ranged between (0.282-3.883) ppb with average value of 1.409 ppb, and between (0.073-2.787) ppb with average value of 1.338 ppb, respectively. The results also showed that the uranium concentration increase with age. On the other side, the average concentrations of uranium in the blood samples for smoker workers is higher than that for non-smoker workers, which conclude that smoking can cause an increase of uranium in the smokerâ€™s blood. All the results revealed that the uranium concentration in the study blood samples were lower than the global permitted value reported by UNSCEAR (1993) and WHO (2001).Â Â Â